Should Allow Future Peruvian Law On Assisted Human Reproduction Techniques The Figure Of "Pregnancy Post Mortem"? - Valverde Morante, Ricardo (2015)
This research paper is presented as working premise to establish whether future Peruvian law on Assisted Human Reproduction Techniques (TERAS), should allow the figure of "Pregnancy Post Mortem", which is regulated in comparative law. Considering that today thanks to the advancement of TERAS is no longer necessary to conceive a child that parents have sex requirement. No obstacle of the above, it is pertinent to note that the proposed reform of our Civil Code has in its text with a chapter on the "Medically Assisted Reproduction affiliation by" which is a novelty in our legal system is a response the existence in our country Clinics lot of Assisted Human Reproduction, who currently operate without pre- established legal parameters. Why, after reviewing the doctrine and the criterion of comparative legislation on "Pregnancy Post Mortem" I fully agree with what is regulated by French law and Italian law. That is, I consider that our Civil Code should not allow "Playing Technique Medicall